River drainage rearrangements and the phylogeographic pattern of the annual fish Austrolebias arachan (Cyprinodontiformes, Rivulidae) - Loureiro, Marcelo; Stareczek, Sofía; D'anatro, Alejandro; Thompson, Andrew W.; Ortí, Guillermo (Zoologica scripta, 2024)
Palaeogeographical and climatic processes are among the main factors affecting biological diversity and distribution patterns. In freshwater systems, major dispersal processes are caused by river drainage rearrangements where the direction of flow of a stream changes, allowing range expansions and connection of previously isolated communities. In the Neotropical region, this process has been known to connect part of the southwestern Amazon basin with La Plata basin during the formation of the Bolivian Orocline, and La Plata basin with Atlantic coastal basins since the split from Africa. Several species of annual fishes of the genus Austrolebias are known to inhabit seasonal ponds both in the Rio Negro basin (southern tip of Brazilian shield, Lower Uruguay ecoregion), and the headwaters of rivers draining into the Merín lagoon (coastal drainages, Laguna dos Patos ecoregion). The aim of this article was to analyse the phylogeographic pattern of Austrolebias arachan in the context of putative river rearrangements. Two hypotheses were tested: (a) the spatial configuration of river basins determines the genetic structure and distribution of this species, and (b) coastal drainages captured sections of upland shield river drainages. We analysed a fragment of the mitochondrial cytochrome b gene and a fragment of a nuclear intron locus. Results support the prediction of the first hypothesis: geographic variation within A. arachan is structured according to geography. The second hypothesis was in part confirmed: the migration analyses showed that Rio Negro basin populations could have acted as a source for Laguna Merin basin. However, migration estimates also support gene flow in the opposite direction. The cytochrome b haplotype network configuration and its phylogenetic pattern suggests at least two independent events of capture, with divergence time estimated at the onset of Pleistocene glacial cycles.